Towards unlocking the trophic roles of rarely encountered squid: Opportunistic samples of Taningia danae and a Chiroteuthis aff. veranii reveal that the Southern Ocean top predators are nutrient links connecting deep-sea and shelf-slope environments - Jackel, Bethany; Baring, Ryan; Doane, Michael P.; Henkens, Jessica; Martin, Belinda; Rough, Kirsten; Meyer, Lauren (Frontiers in Marine Science, 2023)
Deep-sea squids are presumably vital components of largely undescribed marine ecosystems, yet limited access to specimens has hampered efforts to detail their ecological roles as predators and prey. Biochemical techniques such as stable isotope analyses, fatty acid analyses and bomb calorimetry are increasingly recognized for their ability to infer trophic ecology and dietary information from small quantities of tissue. This study used five opportunistically collected Taningia danae specimens and one Chiroteuthis aff. veranii specimen retrieved from the Great Australian Bight, South Australia, to detail the trophic ecology of these poorly understood squids. Four body tissue types (i.e. arm, buccal mass, mantle and digestive gland) were assessed for their utility in SI and FA analyses, and we found that the arm, buccal mass and mantle tissues had similar SI and FA profiles suggesting they can be used interchangeably when the entire specimen is unavailable. 𝛿13C, 𝛿15N and fatty acid data suggests that the T. danae and C. aff. veranii specimens lived in the Southern Ocean and were high trophic level predators, feeding on deep-sea fishes and small squids, whilst also taking advantage of the summer upwelling region of the Great Australian Bight. Fatty acid analysis and bomb calorimetry indicate that these squids might be important reservoirs of essential FAs (EPA and DHA) for Southern Ocean predators and that the whole-body energy content of T. danae individuals can reach up to 362 250 kJ. Our findings indicate that these squids may be contributing greatly to the transport of nutrients and energy between the Southern Ocean deep-sea and Great Australian Bight shelf-slope environments. In addition to building our understanding of the trophic ecology of two poorly understood deep-sea squids, these findings also highlight the utility of partial specimens and demonstrate the important ecological information that can be obtained from few samples that may be opportunistically collected.